Perbedaan Kepekaan Sensivitas Emosi pada Saat Haid dan Tidak Haid - Sinta Murwitasari dan Bimono (LPPM Universitas Proklamasi 45, 2010)
Objective of this study is to understand the difference of emotional sensitivity on girls with menstruation and girls without menstruation. It was about 70 high school students participated in this research. Using the corrcalational t-test statistic analysis (t = 5.234, p< .000), it was rcvelaed that those girls significantly felt higher emotional sensitivity when they were in menstruation periodic (M - 72.05) compare to the situation without menstruation (M = 67.15). The hypothesis was confirmed. The menstruation variable only predicted 28.73% of of the emotional sensitivity. This finding was almost similar with research in Taiwan. For the future research, the lacking of menstruation should be broken down between before and after menstruation. It was because girls on those two menstruation situation felt different emotional sensitivity.